Efficient removal of Cr(VI) at alkaline pHs by sulfite/iodide/UV: Mechanism and modeling. (15th August 2022) - Cong, Yanqing; Shen, Lidong; Wang, Baimei; Cao, Jianlai; Pan, Zixuan; Wang, Ziyu; Wang, Kai; Li, Qiangbiao; Li, Xuchun
Highlights: Efficient removal of Cr(Ⅵ) at alkaline pHs was obtained in sulfite/iodide/UV. The process was effective in real surface water and industrial wastewater. Roles of sulfite and iodide were quantified, and the synergy was interpreted. Mechanism of Cr(VI) removal was revealed, and pathways were proposed. A kinetic model was developed, and performed well in real water. Abstract: Efficient removal of toxic hexavalent chromium (Cr(VI)) under alkaline conditions is still a challenge due to the relatively low reactivity of CrO4 2− . This study proposed a new sulfite/iodide/UV process to remove Cr(VI). The removal of Cr(VI) followed pseudo-zero-order kinetics at alkaline pHs, and was enhanced by sulfite and iodide with synergy. Compared with sulfite/UV, iodide in sulfite/iodide/UV showed about 40 times higher concentration-normalized enhancement for Cr(VI) removal, and reduced the requirement of sulfite ([S(IV)]0 /[Cr(VI)]0 of about 2.1:1) by more than 90%. The Cr(VI) removal was accelerated by decreasing pH and by increasing temperature, and was slightly influenced by dissolved oxygen, carbonate, and humic acid. The process was still effective in real surface water and industrial wastewater. Mechanism and pathways of Cr(VI) removal were revealed by quenching experiments, competition kinetic analysis, product identification and quantification, and mass and electron balance. Both eaq − and SO3 − were responsible for Cr(VI) removal, making contributions of about 75% and 25%, respectively. When eaq − mainly reacted with Cr(VI), SO3 − participated in reduction of Cr(V) and Cr(IV) intermediates, with Cr(III), S2 O6 2−, and SO4 2− as the final products. A model was developed to predict removal kinetics of Cr(VI), and well interpreted the roles of S(IV) and iodide in the process. This study sheds light on mechanism of Cr(VI) removal at alkaline pHs by kinetic modeling, and thus advances the applicability of this promising process for water decontamination. Graphical abstract: Image, graphical abstract